(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Literature belongs not to an age but to all ages. The same is true with Kamala Markandaya’s novel Nectar in a Sieve. It is a post-independence novel which depicts the pitiable situation of Indian peasants. Independent India had to face a number of challenges at that time. Poverty was a great problem and there was spirit of despair everywhere. Farmers were suffering a lot due to lack of money and natural calamities. Writer’s novel Nectar in a Sieve tried to spring positive and affirmative attitude in peasants’ dying faith in life. Every character of this novel whether it is major or minor encounters stark reality of life with heroism and never grumbles in adverse conditions. Hope sustains life is the message which the writer conveys in the novel. It has universal appeal and is relevant in present time as today many peasants are committing suicide due to debt though now India has advanced a lot in every field. Thus the novel which was penned to confer ethical support to peasants of that time can be constructive to hopeless desperate farmers of today.